2024
DOI: 10.1021/acsami.4c02205
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Nanocrystals In Situ Encapsulated in TiO2 Microspheres for Stable CO2 Photoreduction in Water

Cong Zou,
Hao Wu,
Mengda He
et al.

Abstract: Photoreduction of carbon dioxide (CO2) into fuels presents a promising approach to mitigate global warming and energy crises. Halide perovskite nanocrystals (NCs) with prominent optoelectronic properties have triggered substantial attention as photocatalysts but are limited by the charge recombination and instability. Here, we develop stable CsPbBr3/titania microspheres (TMs) by in situ growth of CsPbBr3 NCs inside mesoporous TMs through solid-state sintering, which significantly improves the stability of pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A few other stabilization strategies are further highlighted below, wherein the stability of the perovskite catalyst is ensured even without compromising performance. A recent work by Zou et al reported the in situ growth of CsPbBr 3 nanocrystals inside as synthesized microspheres of TiO 2 by employing the solid-state sintering method . This improves the stability of PNCs, making them suitable for photoreduction in water.…”
Section: Photocatalytic Co2 Reduction: Overview and Reaction Factorsmentioning
confidence: 99%
“…A few other stabilization strategies are further highlighted below, wherein the stability of the perovskite catalyst is ensured even without compromising performance. A recent work by Zou et al reported the in situ growth of CsPbBr 3 nanocrystals inside as synthesized microspheres of TiO 2 by employing the solid-state sintering method . This improves the stability of PNCs, making them suitable for photoreduction in water.…”
Section: Photocatalytic Co2 Reduction: Overview and Reaction Factorsmentioning
confidence: 99%
“…CsPbBr 3 QDs and Ag nanoparticles were anchored on the surface of g-C 3 N 4 sheets, which not only accept photo-induced electrons from the CsPbBr 3 QDs, but also act as an electron-transport tunneling to transfer photo-induced electrons to the Ag nanoparticles for the reduction of CO 2 . The catalytic system developed by Zou et al 146 for the in situ growth of CsPbBr 3 NCs within titania microspheres can convert CO 2 efficiently, with S-scheme charge transfer enhancing the separation of electron–hole pairs.…”
Section: Photocatalytic Applications Of Halide Perovskitesmentioning
confidence: 99%